The Influence of Human Resources, Service Process, and Physical Evidence on Customer Satisfaction at Neofit Gym Solo - Lilyana Adi Bintoro; Basuki Nugroho (ProBisnis : Jurnal Manajemen, 2023)
This writing is to analyze the influence of human resources, service processes, and physical evidence on customer satisfaction at Neofit Gym Solo. The research method used is quantitative research using surveys and interviews, which is intended to provide an explanation. Survey research itself is research that takes samples from a population and uses a questionnaire as the main collection tool. sampling using purposive sampling method in which the sampling technique is carried out with certain considerations or criteria. The study involved 40 customers as respondents. The data were analyzed using a multiple linear regression model using the SPSS v23 application. The results of data compensation show that human resources have a significant effect on customer satisfaction at Neofit Gym Solo with a value of 0.000, service processes and physical evidence have a significant effect on customer satisfaction at Neofit Gym Solo with a significant value of 0.000